"I'm Ready to Eat and Grab Whatever I Can Get": Determinants and Patterns of African American Men's Eating Practices. Issue 2 (March 2013) - Griffith, Derek M.; Wooley, Alana M.; Allen, Julie Ober
This article examines determinants and patterns of African American men's dietary practices. Thematic content analysis was used to analyze data from nine exploratory focus groups conducted with 83 urban, middle-aged and older African American men from southeast Michigan. The men distinguished between healthy and unhealthy foods and "meals" versus other instances of eating. Eating patterns and content differed depending on the meal, work and family schedules, food availability, and whether it was a weekday or weekend. When eating alone or outside the home, men prioritized convenience and preferences for tasty, unhealthy foods. Men often reported skipping breakfast or lunch and grabbing snacks or fast food during the day. They emphasized sharing dinner with their spouses and families—usually a home-cooked, "healthy" meal. On weekends, spouses often cooked less and men snacked and dined out more frequently. Sunday dinners involving favorite, unhealthy comfort foods were the highlight of men's eating practices. African American men tended not to follow healthy eating recommendations because of their busy lives, reliance on spouses to prepare food, and preferences for unhealthy foods. These findings suggest that healthy eating interventions must consider how the contexts of African American men's lives shape their eating practices.